2010
DOI: 10.1002/bsl.902
|View full text |Cite
|
Sign up to set email alerts
|

Reality check: A comparison of college students and a community sample of mock jurors in a simulated sexual violent predator civil commitment

Abstract: Despite concerns about generalizability, past mock trial research has concluded that effects of sample (i.e., students versus representative mock jurors) are negligible. The current study was conducted to explore this conclusion within the conceptual framework of cognitive-experiential self-theory (CEST). Through a mock civil commitment hearing of a sexually violent predator, responses of student (n = 138) and representative (n = 240) mock jurors were compared. Results revealed several important differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 39 publications
(57 reference statements)
6
74
3
Order By: Relevance
“…Future research in this area should ideally use community, rather than student, samples (see Keller & Wiener, 2011;McCabe, Krauss, & Lieberman, 2010). In this sample, racial attitudes were neutral and not particularly variable, which may account for the lack of findings with regards to racial attitudes.…”
Section: Limitations and Future Directionsmentioning
confidence: 89%
“…Future research in this area should ideally use community, rather than student, samples (see Keller & Wiener, 2011;McCabe, Krauss, & Lieberman, 2010). In this sample, racial attitudes were neutral and not particularly variable, which may account for the lack of findings with regards to racial attitudes.…”
Section: Limitations and Future Directionsmentioning
confidence: 89%
“…McCabe and found that a community sample had higher rational scores (i.e., NFC) and higher experiential (i.e., FI) scores than students-but the two groups were examined in two different studies so no direct statistical comparison was made. In contrast, McCabe, Krauss, and Lieberman (2010) found that students scored higher on the NFC measure than community members. Furthermore, whether NFC and FI are related to legal decision making might depend on the identity of the decision maker.…”
Section: Students Versus Community Membersmentioning
confidence: 91%
“…The question debated in the field of psychology and law is whether those aspects influence legal decision-making, or even decision-making in only certain types of cases (Bornstein, 1999;Diamond, 1997;Wiener, Krauss, & Lieberman, 2011). Compared with community members called for jury duty, undergraduate students are usually younger, of relatively high SES, have higher need for cognition (i.e., the extent to which people enjoy effortful thinking; Cacioppo & Petty, 1982), and are less likely to be parents (McCabe, Krauss & Lieberman, 2010;Sears, 1986;Quas, Thompson, & Clarke-Stewart, 2005). But there is little evidence that these factors are linked to decision-making in child sexual abuse cases (e.g., McCauley & Parker, 2001).…”
Section: Methodsmentioning
confidence: 99%